THE IMPACT OF CYBERBULLYING ON ADOLESCENT MENTAL HEALTH, AND LAW ENFORCEMENT IN INDONESIA - Rofi’i; Budi Parmono; Rahmatul Hidayati (International Journal of Cultural and Social Science, 2025)
This study focuses on the psychosocial and academic impacts experienced by high school students as victims of cyberbullying. The main objective of this study is to identify the forms of digital bullying experienced by students and explore the emotional and social responses that arise as a result of the incident. Using a qualitative approach with a case study method, data were collected through in-depth interviews with five students who were victims of cyberbullying, direct observation in the school environment, and supporting documentation. The results of the study showed that all respondents experienced psychological stress such as deep shame, excessive anxiety, and fear in social interactions, both online and offline. In addition, cyberbullying also has an impact on decreased concentration in learning, academic achievement, and reluctance to participate in school activities. The variation in social support received by victims also shows a significant gap in the student assistance and protection system at school. The implications of this study emphasize the importance of collaborative interventions between schools, families, and digital communities to build a comprehensive detection, assistance, and recovery system for victims of cyberbullying. This study also recommends strengthening digital literacy and legal education as part of a long-term preventive strategy.